Translation and cross-cultural adaptation of the Yale Pharyngeal Residue Severity Rating Scale into Brazilian Portuguese - Venite, Roberta Seabra [UNESP]; Pernambuco, Leandro; Silva, Roberta Gonçalves da [UNESP]; Onofri, Suely Mayumi Motonaga [UNESP] (Elsevier, 2024)
Objective: To report the process of translation and cross-cultural adaptation of theYale Pharyngeal Residue Severity Rating Scale into Brazilian Portuguese. Methods: Methodological study approved by the Ethics Committee of the Institution (nº 5.166.256). The English original scale was translated into Brazilian Portuguese following suggested in the literature guidelines and recommendations after authorization from the authors of the original instrument, and involved the following reported steps of (1) Translation, (2) Synthesis of translations, (3) Determination of the applicability of the translated version 4) Back-translation, (5) Synthesis of the back-translated versions, and (6) Final synthesis. The translations and back-translations were performed by two bilingual translators. The research committee constituted three specialists who considered whether the linguistic, semantics, conceptual, idiomatic, and contextual equivalence of the translations and back-translations were. In Step 3, the raters consisted of three Speech-Language Pathologists and five ENT physicians divided into two subgroups (less than 5 years of professional expertise, and more than 5 years of professional expertise). Results: Step 1 was carried out properly by the translators, in Step 2 the translated version was prepared after minor adjustments. In Step 3, the raters reported that they found no difficulties in applying the scale. The Cronbach's Alpha coefficient was 0.995, demonstrating high internal consistency of the instrument, and the analysis of the Intraclass Correlation Coefficient (ICC) among the eight raters was 0.994 with a confidence interval between 0.990 and 0.998, demonstrating excellent agreement, regardless of experience. The research committee judged the last to be adequate and not to require adjustments. Conclusion: The Brazilian Portuguese version of theYale Pharyngeal Residue Severity Rating Scale is presented in this study. This is a methodological study – No level of evidence.
Keywords: Back-translation; Cross-cultural comparison; Deglutition; Endoscopy; Translation